2018
DOI: 10.1159/000489547
|View full text |Cite
|
Sign up to set email alerts
|

An Intersectional Study of LncRNAs and mRNAs Reveals the Potential Therapeutic Targets of Buyang Huanwu Decoction in Experimental Intracerebral Hemorrhage

Abstract: Background/Aims: Both experimental and clinical studies have revealed satisfactory effects of the traditional Chinese formula Buyang Huanwu decoction (BYHWD) in improving post-intracerebral hemorrhage (ICH) neurological deficiencies. However, the multifaceted mechanisms of BYHWD in ICH treatment are not comprehensively understood. The present study explored various therapeutic targets of BYHWD by using lncRNA and mRNA transcriptomics. Methods: LncRNA and mRNA microarrays were used to identify differentially ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 57 publications
0
17
0
Order By: Relevance
“…Cui et al [26] identified differentially expressed genes in Buyang Huanwu decoction intracerebral hemorrhage treatment with lncRNA and mRNA microarray technology and verified the results by qRT-PCR. The biological functions and signal transduction pathways of the differentially expressed genes were analyzed and were found to be related to hemoglobin complexes, oxygen transporters, oxygen transporters, and pyruvate metabolism.…”
Section: Application Of Transcriptomics In Chf Researchmentioning
confidence: 94%
“…Cui et al [26] identified differentially expressed genes in Buyang Huanwu decoction intracerebral hemorrhage treatment with lncRNA and mRNA microarray technology and verified the results by qRT-PCR. The biological functions and signal transduction pathways of the differentially expressed genes were analyzed and were found to be related to hemoglobin complexes, oxygen transporters, oxygen transporters, and pyruvate metabolism.…”
Section: Application Of Transcriptomics In Chf Researchmentioning
confidence: 94%
“…Furthermore, each herb was authenticated by the herbal medicinal botanist, Professor Suiyu Hu, at the Institute of Integrative Medicine of Xiangya Hospital, CSU. The decoction was prepared and subjected to quality control as previously described 26. Finally, the powder was dissolved in distilled water at a concentration of 0.13 g/ml for intragastric administration 26.…”
Section: Methodsmentioning
confidence: 99%
“…The decoction was prepared and subjected to quality control as previously described 26. Finally, the powder was dissolved in distilled water at a concentration of 0.13 g/ml for intragastric administration 26.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations